Dynamic Railcar Flow Assignment of Railway Terminal with Multiple Marshalling Stations - Xiaoqian Zhou; Bing Li; Zeqiang Ren; Ziao Cao (Systems)
This paper deals with the optimization of railcar flow assignment among multiple marshalling stations oriented to making a stage plan. We aimed to minimize the total dwell time of the on-time and delayed allocated railcar flow at the station within a stage plan. Considering the limitations of the disassembly and assembly capacity of marshalling stations, the limitation of the transfer operation capacity between marshalling stations, the connection time limit of inbound and outbound trains, and the limitation of trains with different full workloads, we constructed a multi-marshalling station railcar flow assignment optimization model. Furthermore, for comparison, we built a model that only satisfied the train equivalent length limitation and a model that only satisfied the train hauling weight limitation. Finally, we designed experimental scenarios and conducted comparative analyses of the proposed model and a model that considered only a single full workload limitation. The results show that the railcar flow assignment scheme that considers different full workload limitations shortens the dwell time of railcar flow at the station, reduces the number of undispatched outbound trains within the time range of the stage plan, and effectively improves the terminal operation efficiency within the stage plan. Thus, the proposed scheme can achieve an effective railcar flow assignment within a multi-marshalling station railroad terminal while minimizing the dwell time.